From the frontier to the city: The transformation of the imperial court in the age of the Theodosian dynasty (379-457) - JOSEPH MOORE (2024)
Beyond acting as a residence for the monarch, a royal court serves as a physical, sociological, and ideological space within which the authority of the monarch was negotiated and reinforced. The analysis of the late Roman court as a sociological institution beyond its governing function has been a relatively recent development in Late Antique Scholarship. As such, scholars have too often analysed it as a static institution, failing to appreciate profound developments throughout this period. My thesis will identify one of most important, the shift from a mobile to sedentary court, which I identify as a product of the Theodosian dynasty (379-457). The unique dynamics of Theodosius I’s accession in 379 necessitated a change in the nature of the court, settling the court in a fixed residence. This resulted in a long-term shift away from the mobile court of earlier dynasties to a sedentary court centred in Constantinople in the east, and Milan and then Ravenna and Rome in the west. My thesis will analyse this shift and the impact it had. I first consider the contradictory images of the imperial court that are presented by the primary sources. I then analyse the shift from a mobile court to a sedentary court. After that I argue that this resulted in the elaboration of more complex forms of court ceremonial. Finally, I explore the relationship between the imperial court and one of the main institutions with which it now shared the urban space, the Church. My project will incorporate a variety of primary sources, including narrative sources, oratory, administrative documents, and material evidence. Ultimately, I anticipate that this research will help to inform scholarly debate concerning the late antique imperial court and the nature of imperial power.